"Devalued" Daughters Versus "Appreciated" Sons: Gender Inequality in China's Parent-Organized Matchmaking Markets. (September 2017) - Gui, Tianhan
Postponed marriage is a general trend among today's Chinese young people. However, since in traditional Chinese culture, marriage has been regarded as a family responsibility, when adult children reach a certain age, their parents often push them for marriage. In recent years, some retired parents in China's major cities voluntarily organized matchmaking markets in parks to exchange their single adult children's personal information in order to "help" the latter find spouse. Most of these matchmaking markets are only attended by parents, whose adult children remain single in their late 20s and beyond. Through a field research on matchmaking events held in four parks in Beijing, it was found that young women's parents significantly outnumbered young men's parents. Younger age and good physical appearance are considered as "assets" for women, while men's most valued "capital" are better education, higher income, and wealth.